Digital devices usage barriers among community-dwelling older adults in Abha, Saudi Arabia: A cross-sectional study - Hawash, Manal Mohammed (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Modern communities increasingly rely on technology, influencing older adults’ health and daily life. While technology can enhance quality of life and independence, various barriers limit digital adoption among older adults. Objective: This study aimed to identify barriers to digital device use among community-dwelling older adults in Abha, Saudi Arabia. Methods: This study used a cross-sectional survey of 400 adults aged 60 years and older. Data were collected from February to March 2025 on depression (Beck Depression Inventory-II), cognitive status (Saint Louis University Mental Status Examination), and technology-related barriers (Technology Usage Barriers Questionnaire). Data were analyzed using t-tests, one-way ANOVA, effect sizes (Cohen’s d, η²), and 95% confidence intervals. Results: Smartphone users reported significantly higher barriers than feature phone users in personal (8.07 ± 4.50 versus 5.70 ± 5.09; p <0.001; d= 0.50), technical (5.20 ± 4.60 versus 4.20 ± 3.02; p = 0.009; d = 0.25), and environmental domains (1.90 ± 1.30 versus 1.40 ± 1.50; p = 0.001; d = 0.36). Among smartphone users, the highest personal barriers were observed in adults aged 80 years and older (11.3 ± 4.3; η² = 0.075), females (d= 0.48), those with primary education (d = 0.84), low-income individuals (d = 0.44), unemployed participants (d = 1.23), and rural residents (d = 1.24). Education most strongly predicted technical barriers (d = 0.94), while income had the greatest impact on environmental barriers (d = 0.93). Conclusion: Older adults, especially smartphone users, women, those with lower education, low income, unemployed individuals, and rural residents, face substantial barriers to digital adoption. Tailored digital literacy programs, affordable access, and senior-friendly device design are essential to reduce the digital divide and improve autonomy, inclusion, and quality of life. For nursing practice, these findings emphasize the importance of assessing older adults’ digital skills, providing targeted education, and advocating for technology solutions that support engagement and health management.